Solar Analysis Using Building Information Modelling with the Glass Box Method in Jakarta - Riva Tomasowa (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The utilisation of Building Information Modelling (BIM) focuses more on the Schematic Design or Technical Design phase, while the Preliminary or the Conceptual design is pretty much skipped. This paper shows that a simple model could utilise BIM to gain rich information about solar radiation to give ideal orientation in Preliminary phase. On this case, a spot in Jakarta is analysed with Glass Box method to depict the ideal orientation that receive a minimum solar radiation in a year span.